Silver Jubilee ! - Assoumou Mba, D. (Technical Centre for Agricultural and Rural Cooperation, 1990)
We have cause to celebrate this month because this is the 25th issue of SPORE. For 50 months now since February 1986 the circulation of our bulletin has grown with each issue. At this milestone in our development, the time has come to pause and look...